Active stabilization of unmanned aerial vehicle imaging platform. (3rd February 2020) - Verma, Mohit; Lafarga, Vicente; Baron, Mael; Collette, Christophe
The advancement in technology has seen a rapid increase in the use of unmanned aerial vehicles for various applications. These unmanned aerial vehicles are often equipped with the imaging platform like a camera. During the unmanned aerial vehicle flight, the camera is subjected to vibrations which hamper the quality of the captured images/videos. The high-frequency vibrations from the unmanned aerial vehicle are transmitted to the camera. Conventionally, passive rubber mounts are used to isolate the camera from the drone vibrations. The passive mounts are able to provide reduction in response near the resonance. However, this comes at the cost of amplification of response at the higher frequency. This article proposes an active vibration isolation system which exhibits improved performance at the higher frequencies than the conventional system. The active isolation system consists of a contact-less voice coil actuator supported by four springs. Experiments are carried out to study the effect of vibrations on the quality of images captured. The characterization of drone vibrations is also carried out by recording the acceleration during different flight modes. The performance of the proposed isolation system is experimentally validated on a real drone camera subjected to the recorded drone acceleration spectrum. The isolation system is found to perform better than the conventional rubber mounts and is able to reduce the vibrations to a factor of one-fourth. It can be effectively used to improve the image acquisition quality of the unmanned aerial vehicles.